2011
DOI: 10.1007/s11427-011-4186-6
|View full text |Cite
|
Sign up to set email alerts
|

Root growth in response to nitrogen supply in Chinese maize hybrids released between 1973 and 2009

Abstract: Root growth has a fundamental role in nitrogen (N) use efficiency. Nevertheless, little is known about how modern breeding progress has affected root growth and its responses to N supply. The root and shoot growth of a core set of 11 representative Chinese maize (Zea mays L.) hybrids released between 1973 and 2009 were investigated under high N (4 mmol L(-1), HN) and low N (0.04 mmol L(-1), LN) levels in a solution culture system. Compared with LN, HN treatment decreased root dry weight (RDW), the root: shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The significant G × E and identified Q × E effect suggested that crop breeder needs to use different selection progress under different nitrogen levels. Wu et al () found that root growth has not improved under low N conditions over the last 36 years of selective breeding in China. Several studies revealed modified root architecture can enhance root uptake (Uga et al ; Mu et al ), and ideotype RSA has been proposed for efficient N acquisition (Mi et al ; Lynch ).…”
Section: Discussionmentioning
confidence: 99%
“…The significant G × E and identified Q × E effect suggested that crop breeder needs to use different selection progress under different nitrogen levels. Wu et al () found that root growth has not improved under low N conditions over the last 36 years of selective breeding in China. Several studies revealed modified root architecture can enhance root uptake (Uga et al ; Mu et al ), and ideotype RSA has been proposed for efficient N acquisition (Mi et al ; Lynch ).…”
Section: Discussionmentioning
confidence: 99%
“…Urea transporting DUR3 proteins also participated in nitrogen remobilization. ciated with nitrogen remobilization [239] [330] [331]. TIP1; 3 and TIP5; 1 are expressed in the mature pollen.…”
Section: Nitrogen Remobilizationmentioning
confidence: 99%
“…P. trichocarpa consists of 6 AMT1 and 8 AMT2 proteins [171]. Rice DUR3 gene codes for a 721 residue long membrane-protein and showed similar expression and regulation patterns as that of Arabidopsis DUR3 gene [239] [240].…”
Section: Plant Nitrome (Nitro (Gen)ome)mentioning
confidence: 99%
“…Because of the great differences in growth period and pattern between the old and new rice cultivars, it is difficult to clarify how genetic improvements contribute to root growth in rice. For example, for a solution culture system, Wu et al suggested that total root length increased with increasing year of release for maize hybrids, while shoot dry weight, root dry weight and leaf area decreased (Wu et al, 2011). However, using similar materials to Wu et al in the field, Chen et al reported that dry matter production had increased, and modern maize since 1990 had reduced root length density (Chen et al, 2014).…”
mentioning
confidence: 99%
“…The decreasing LN/HN ratio (r=−0.4334)also suggest that roots of the new super rice cultivars were less responsive to LN ( Figure 1A). Modern rice cultivars are commonly selected under high nutrient supply, resulting in their high tolerance to high N rates and less response of root growth to low N (Wu et al, 2011). Adventitious root length showed no change in the cultivars prior to the 1980s, but was decrease in later cultivars for LN ( Figure 1G).…”
mentioning
confidence: 99%